Como o ensino de cosmologia pode contribuir para o desenvolvimento de atitudes transdisciplinares nos alunos? - Dopico, Sabrina Isis Bruganarotto (2019)
The objective of the research that was developed in this dissertation was to identify how the teaching of cosmology contribute for the formation of transdisciplinary attitudes in students. This research was developed because of the importance of transdisciplinarity for incentivated the reflexions in the students together with the Cosmology that elucidates a theme incentivator of thisreflections. Apart from that very students demonstrated interest for Cosmology. For that initially was readed books of the autores Edgar Morin, Basarab Nicolescu, Dinorah Sanvitto Tronca and one thesis that describes the indicators of transdisciplinary attitudes. Done that, We searched in databases of thesis and dissertations for the selection of papers that related to the theme of cosmology teaching. For the data collection and analysis was utilized the bibliographic research and the dialectical critical analisys based on differents books for a better understanding of your stages. So the question research was been formuled like: How the theaching of Cosmology can contribute for the formation of transdisciplinary atitudes in students? We show that from the analysis of the data base selected the transdisciplinary attitudes can be developed from teaching of Cosmology wich exception one of this attitudes. Yet for the atittudes be manifested in students the approaches used for the teachers don’t be a traditional approaches or superficials. The attitudes can manifested in the students from visions wich the science it’s not finished but chanching. This vision developed from the study how the cosmologic models evolved from the history of the humanity. Therefore thaking into account wich the Science knowledge is product of the interation of distints levels of reality.The transdisciplinar atitudes also manifested to visions more open about the science enad religion in the science story. The dialeticals process in students contributed so that they arrive to elaborated consensus envolving the principals controversies in the Cosmology.